Frequency of Sleep Pattern Abnormalities among End Stage Renal Disease Patients on Maintenance Hemodialysis - Azam, Aftab; Anwar, Shahid; Akram, Mateen; Ahmad, Sajad; Usman, Hafiz Tahir; Anwar, Zahid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: End-stage renal disease patients getting hemodialysis (HD) frequently report sleep problems. There are various sorts of sleep disorders, generally classified into different categories depending upon initiation of sleep, duration, and continuity of sleep, calmness during sleep, respiration pattern during sleep, and daytime alertness. Sleep abnormalities have a significant and well-documented effect on daily routine activities thereby reducing the quality of life. Objective: To determine the frequency of sleep pattern abnormalities in patients with chronic kidney disease on maintenance hemodialysis. Study Design: Cross-sectional study Place and Duration of Study: Department of Nephrology, Sir Ganga Ram Hospital, Lahore from 24th January 2019 to 24th July 2019. Methodology: Ninety one cases ages between 14-70 years of either gender, having ESRD, and are on maintenance HD for at least 3 months were included. All those patients who were having HD for acute kidney injury were excluded. Sleeping disorders were evaluated using Pittsburgh Sleep Quality Index by a single interviewer. Results: Fifty five (60.4%) were males and 36 (39.6%) were females. The mean age was 51.1±12.1 years, mean BMI was 25.1±5.2, and mean duration of dialysis was 5.1±2.8 years, 74(81.3%) patients had sleep disorders. Among patients having sleep disorders, 38(41.8%) had Insomnia, Narcolepsy in 41(51.6%), Sleep Apnoea Syndrome in 38(41.8%), restless leg syndrome in 35(38.5%) and parasomnia in 17(18.7%) patients. Conclusion: Sleep disorders are common in regular hemodialysis patients affecting 81.3% of individuals.